2020
DOI: 10.21203/rs.2.12890/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of acupuncture in improving the symptoms and the quality of life of patients with moderate or severe acne vulgaris: a protocol for a randomized controlled trial

Abstract: Background : Acne vulgaris (AV) is a common chronic dermatologic disease that tends to impair the appearance and the quality of life (QoL) of patients. Although several trials have indicated the effectiveness of acupuncture for treatment of patients with AV, the results of these trials have been contested owing to potential bias in their design. Thus, there is a lack of robust data to evaluate the efficacy of acupuncture in patients with AV. In addition, none of the previous clinical trials of acupuncture ther… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The trial protocol has been described in detail elsewhere. 13 The study conformed to the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) 14 and the STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) 15 guidelines. Participants were recruited by advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…The trial protocol has been described in detail elsewhere. 13 The study conformed to the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) 14 and the STandards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) 15 guidelines. Participants were recruited by advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…Various clinical investigations have been conducted to examine the potential of acupuncture therapy on patients with acne 51‐55 . The exact functioning of acupuncture in acne treatment is still unsettled; however, based on the research analysis, acupuncture includes the hypothalamus‐pituitary‐adrenal Axis, brain‐derived neurotrophic factor, and the autonomic nervous system 56 .…”
Section: Acupuncture and Methodsmentioning
confidence: 99%
“…48 Various clinical investigations have been conducted to examine the potential of acupuncture therapy on patients with acne. [51][52][53][54][55] The exact functioning of acupuncture in acne treatment is still unsettled; however, based on the research analysis, acupuncture includes the hypothalamus-pituitary-adrenal Axis, brain-derived neurotrophic factor, and the autonomic nervous system. 56 Furthermore, it also acts as an immune system modulator, which is supported by different studies 57,58 The studies have shown successful acne treatment on a distinct number of populations, and utilizing different methods includes acupuncture anesthesia on acne vulgaris of prickingbloodletting cupping, 59 warm needling method for keloidal acne, 60 fire needle therapy, 61 sham acupuncture on severe acne vulgaris, 51 and ah shi point acupuncture on acne vulgaris.…”
Section: Acupun C Ture and Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation